CBD Effects on Motor Profile and Neurobiological Indices Related to Glutamatergic Function Induced by Repeated Ketamine Pre-Administration - Poulia, Nafsika; Delis, Foteini; Brakatselos, Charalampos; Ntoulas, George; Asprogerakas, Michail-Zois; Antoniou, Katerina (Frontiers in Pharmacology, 2021)
Clinical evidence and experimental studies have shown the psychotomimetic properties induced by ketamine. Moreover, acute or chronic ketamine (KET) administration has been widely used for modeling schizophrenia-like symptomatology and pathophysiology. Several studies have reported the antipsychotic potential of cannabidiol (CBD), while there is limited information on the cannabidiol effect on KET-induced schizophrenia-like impairments. Therefore, the goal of the present study was to evaluate neuroplastic changes induced by repeated KET administration, which is used as an experimental model of schizophrenia – with a behavioral focus on positive-like symptomatology– and to assess the modulatory role of CBD treatment. The present findings have shown a robust increase in motor activity in KET-treated rats, following a 10-day period of chronic administration at the sub-anesthetic dose of 30 mg/kg (i.p), that was reversed to normal by subsequent chronic CBD treatment. Concerning the expression of glutamate receptors, the current findings have shown region-dependent KET-induced constitutional alterations in NMDA and AMPA receptors that were modified by subsequent CBD treatment. Additionally, repeated KET administration increased ERK1/2 phosphorylation state in all regions examined, apart from the ventral hippocampus that was modulated by subsequent CBD treatment. The present results show, for the first time, a stimulated motor output coupled with a specific glutamatergic-related status and ERK1/2 activation following chronic KET administration that were attenuated by CBD treatment, in a region-dependent manner. These findings provide novel information concerning the antipsychotic potential of CBD using a specific design of chronic KET administration, thus contributing to experimental approaches that mirror the symptomatology and pathophysiology of schizophrenia.